IMPLEMENTATION OF PERSONALITY COMPETENCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN THE INTEGRATED ISLAMIC ELEMENTARY SCHOOL SYARIF ARRASYID ISLAMIC SCHOOL MEDANACADEMIC YEAR 2017/2018 - Reza Noprial Lubis (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
Personality competence is a skill or ability that must be possessed bysomeone, especially the teacher. Some of the competence of teachers isalready owned by PAI teachers in Syarif Ar-Rasyid Islamic SchoolMedan's Integrated Islamic Elementary School. But there are also thosewho have not implemented personality competence fully, as seen there are teachers who have not been mature, meaning that they cannot prioritize obligations over their personal interests, and there are still teachers whoare not respected by their students and there are still teachers who seemindifferent to problems or problems faced by learners, and still appear tobe undisciplined in the time or hours of entering class. This affects thepersonality of students at SDIT Syarif Ar-Rasyid Islamic School. Good orbad personal learners, depending on the good and bad personal teacherwho guides them. This research is located at SDIT Syarif Ar-RasyidIslamic School which is located at Jalan Menteng VII No. 186 Medan City.The type of research used is a type of qualitative research, namely the typeof research that examines data that can describe complex and concretesocial realities. Qualitative research is a research procedure that generatesdescriptive data about people through written or spoken words andobservable behavior. The results of this study are that compliance with theRepublic of Indonesia Law No. 14/2005 concerning Teachers andLecturers at the Syarif Ar-Rasyid Islamic School Integrated IslamicElementary School Medan. PAI teacher at SDIT Syarif Ar-Rasyid IslamicSchool has not met the standards as intended in the Law of the Republic ofIndonesia Number 14 of 2005 concerning Teachers and Lecturers article 10paragraph 1. The indicators which have not been fully implementednamely; (1) a stable and stable personality; (2) mature person. There arealso some additional indicators that exist in the PAI teacher at SDIT SyarifAr-Rasyid Islamic School Medan, including: (1) devotion (doing Ibadanconsistently); (2) attention to students; (3) getting along with studentsgently; (4) do not smoke.